Isolation and Characterization of Neural Crest-Derived Stem Cells From Adult Ovine Palatal Tissue - Zeuner, Marie-Theres; Didenko, Nikolai N.; Humphries, David; Stergiadis, Sokratis; Morash, Taryn M.; Patel, Ketan; Grimm, Wolf-Dieter; Widera, Darius (Frontiers in Cell and Developmental Biology, 2018)
Adult mammalian craniofacial tissues contain limited numbers of post-migratory neural crest-derived stem cells. Similar to their embryonic counterparts, these adult multipotent stem cells can undergo multi-lineage differentiation and are capable of contributing to regeneration of mesodermal and ectodermal cells and tissues in vivo. In the present study, we describe for the first time the presence of Nestin-positive neural crest-derived stem cells (NCSCs) within the ovine hard palate. We show that these cells can be isolated from the palatal tissue and are able to form neurospheres. Ovine NCSCs express the typical neural crest markers Slug and Twist, exhibit high proliferative and migratory activity and are able to differentiate into α smooth muscle cells and β-III-tubulin expressing ectodermal cells. Finally, we demonstrate that oNCSCs are capable of differentiating into osteogenic, adipogenic and chondrogenic cells. Taken together, our results suggest that oNCSCs could be used as model cells to assess the efficacy and safety of autologous NCSC transplantation in a large animal model.